MENU
Question -

Expand each of the following, using suitable identities:

(i) (x+2y+4z)_2

(ii) (2x−y+z)_2

(iii) (−2x+3y+2z)_2

(iv) (3a –7b–c)_2

(v) (–2x+5y–3z)_2

(vi) ((1/4)a-(1/2)b +1)_2



Answer -

(i) (x+2y+4z)2

Using identity, (x+y+z)2 = x2+y2+z2+2xy+2yz+2zx

Here, x = x

y = 2y

z = 4z

(x+2y+4z)= x2+(2y)2+(4z)2+(2×x×2y)+(2×2y×4z)+(2×4z×x)

= x2+4y2+16z2+4xy+16yz+8xz


(ii) (2x−y+z)2 

Using identity, (x+y+z)2 = x2+y2+z2+2xy+2yz+2zx

Here, x = 2x

y = −y

z = z

(2x−y+z)= (2x)2+(−y)2+z2+(2×2x×−y)+(2×−y×z)+(2×z×2x)

= 4x2+y2+z2–4xy–2yz+4xz


(iii) (−2x+3y+2z)2

Using identity, (x+y+z)2 = x2+y2+z2+2xy+2yz+2zx

Here, x = −2x

y = 3y

z = 2z

(−2x+3y+2z)= (−2x)2+(3y)2+(2z)2+(2×−2x×3y)+(2×3y×2z)+(2×2z×−2x)

= 4x2+9y2+4z2–12xy+12yz–8xz


(iv) (3a –7b–c)2

Using identity (x+y+z)2 = x2+y2+z2+2xy+2yz+2zx

Here, x = 3a

y = – 7b

z = – c

(3a –7b– c)= (3a)2+(– 7b)2+(–c)2+(2×3a ×– 7b)+(2×– 7b ×– c)+(2×– c ×3a)

= 9a2 + 49b+ c2–42ab+14bc–6ca


(v) (–2x+5y–3z)2

Using identity, (x+y+z)2 = x2+y2+z2+2xy+2yz+2zx

Here, x = –2x

y = 5y

z = – 3z

(–2x+5y–3z)= (–2x)2+(5y)2+(–3z)2+(2×–2x× 5y)+(2× 5y×– 3z)+(2×–3z ×–2x)

= 4x2+25y+9z2–20xy–30yz+12zx


(vi)((1/4)a-(1/2)b+1)2

Using identity, (x+y+z)2 = x2+y2+z2+2xy+2yz+2zx

Here, x = (1/4)a

y = (-1/2)b

z = 1

Comment(S)

Show all Coment

Leave a Comment

Free - Previous Years Question Papers
×